If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -0.25(x + -8) + -1 Reorder the terms: y = -0.25(-8 + x) + -1 y = (-8 * -0.25 + x * -0.25) + -1 y = (2 + -0.25x) + -1 Reorder the terms: y = 2 + -1 + -0.25x Combine like terms: 2 + -1 = 1 y = 1 + -0.25x Solving y = 1 + -0.25x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 1 + -0.25x
| 12*50= | | 6x+6z=7+5y | | -20+18t=-(6t-4) | | 5x+7z=2+7y | | 5sinx+7cosx=2 | | V(x)=x(5-2x)(10-2x) | | 7sinx+7cosx^2=7 | | 2g+5=1g-4 | | a^2+b^2=40000 | | 2(x+5)(x-2)=x(x+5)+90 | | -6x^2-3x-3=0 | | 3x-8=2+4x-8 | | 7x-3(c+6)=14 | | 26x+4=18 | | 2x=80-2x | | 0.36/8 | | 10n^2-29n-44=0 | | 445-6x=0 | | -34z=14 | | -((2x)/(x-1)^3)=0 | | 4x^2-49x-900=0 | | 4x-9-6x=2(x+5)-3 | | 0.5x+0.3=.2 | | -5x-12y=15 | | 6*6/2(3)=4 | | -0.5(x-2)=-x-2 | | 2(x-16)=0 | | -((20x)/sqrt(9-20x^2)=2 | | y/8-x/4=1 | | 13x-1=116 | | y=2x^2+(4)x-7 | | -((20x)/(9-20x^2)^(1/2))=2 |